Barriers of effective health insurance coverage for rural-to-urban migrant workers in China: a systematic review and policy gap analysis - Shanquan Chen; Yingyao Chen; Zhanchun Feng; Xi Chen; Zheng Wang; Jianfeng Zhu; Jun Jin; Qiang Yao; Li Xiang; Lan Yao; Ju Sun; Lu Zhao; et al. (BMC, 2020)
Abstract Background More than 90% of the Chinese population was covered by its three basic social health insurances. However, the Chinese rural-to-urban migrant workers (RUMWs), accounting for about one-fifth of China's total population, seem to be put on a disadvantaged position under the current health insurance schemes. The purpose of this study is to identify the current barriers and to provide policy suggestions to the ineffective health insurance coverage of RUMWs in China. Methods A systematic review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The searched databases included PubMed, Embase, Medline, Web of Science, PsycINFO, Maternity and Infant Care Database MIDIRS, the Cochrane Library, WHO Library Database (WHOLIS), WHO Global Health Library, World Bank eLibrary, OpenGrey, CNKI, and Wanfang. In total, 70 articles were reviewed. Results (1) Chinese RUMWs have high work mobility and low job stability; (2) Barriers faced by RUMWs in obtaining effective health insurance coverage are primarily due to the reluctance of employers to provide insurance for all employees and the disadvantaged position held by RUMWs when negotiating with their employers; (3) Fissures among existing health insurance schemes leaves no room for RUMWs to meet their primary needs; and (4) Recent efforts in improving the portability and transferability of insurance across borders and schemes are not enough to solve the barriers. Conclusion It is argued that the Chinese central government must deal with the fragmentation of healthcare system in China and promote effective coverage by: (1) playing a more active role in coordinating different healthcare and social welfare schemes across the country, (2) increasing the health insurance portability, (3) making the healthcare policies more compatible with RUMW's characteristics to meet their primary health needs, (4) strengthening supervision of employers, and (5) providing more vocational training and other support to increase RUMW's job stability.